2021
DOI: 10.1002/acn3.51273
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β, cortical thickness, and subsequent cognitive decline in cognitively normal oldest‐old

Abstract: Objective To investigate the relationship between amyloid‐β (Aβ) deposition and markers of brain structure on cognitive decline in oldest‐old individuals with initial normal cognition. Methods We studied cognitive functioning in four domains at baseline and change over time in fifty‐seven cognitively intact individuals from the EMIF‐AD 90+ study. Predictors were Aβ status determined by [18F]‐flutemetamol PET (normal = Aβ − vs. abnormal = Aβ+), cortical thickness in 34 regions and hippocampal volume. Mediation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Slower rates of memory decline have also been associated with larger baseline whole brain volume across the older adult lifespan (Carmichael et al, 2012). Cross-sectional studies similarly report that oldest-old adults with larger hippocampus volumes have better episodic memory performance (Eguchi et al, 2019) and faster processing speeds (Legdeur et al, 2020;Pelkmans et al, 2021), comparable to what has been reported in younger-old adults (Carr et al, 2017;Gorbach et al, 2017;O'Shea et al, 2016).…”
Section: Neurocognitive Aging In the Oldest-oldmentioning
confidence: 65%
See 3 more Smart Citations
“…Slower rates of memory decline have also been associated with larger baseline whole brain volume across the older adult lifespan (Carmichael et al, 2012). Cross-sectional studies similarly report that oldest-old adults with larger hippocampus volumes have better episodic memory performance (Eguchi et al, 2019) and faster processing speeds (Legdeur et al, 2020;Pelkmans et al, 2021), comparable to what has been reported in younger-old adults (Carr et al, 2017;Gorbach et al, 2017;O'Shea et al, 2016).…”
Section: Neurocognitive Aging In the Oldest-oldmentioning
confidence: 65%
“…Several studies have shown that fewer WMH and better microstructure (e.g., higher FA, lower diffusivity) relates to better cognitive performance into advanced age, with the most studied cognitive domains being episodic memory, executive functions, and processing speed (Table 2). For example, within oldest-old adults, those with slower rates of memory decline also had fewer baseline WMH across the brain (Pelkmans et al, 2021). Better episodic memory performance has also been related specifically to better medial temporal white matter microstructure (65-98 years; Merenstein et al, 2021), as well as better hippocampal gray matter microstructure across the older adult (56-99 years; Reas et al, 2021) and entire (4-93 years; Langnes et al, 2020) lifespan.…”
Section: Neurocognitive Aging In the Oldest-oldmentioning
confidence: 99%
See 2 more Smart Citations
“…Slower rates of episodic memory decline assessed longitudinally have been reported within oldest-old adults with fewer changes in hippocampal volume (Legdeur et al, 2019) and higher baseline medial temporal and anterior cingulate cortical thickness (Pelkmans et al, 2021). Slower rates of memory decline have also been associated with larger baseline whole brain volume across the older adult lifespan (Carmichael et al, 2012).…”
Section: Neurocognitive Aging In the Oldest-oldmentioning
confidence: 99%